Naturally Acquired Human Plasmodium cynomolgi and P. knowlesi Infections, Malaysian Borneo - Thamayanthi, Nada Raja; Ting, Huey Hu; Khamisah, Abdul Kadir; Dayang Shuaisah, Awang Mohamad; Nawal, Rosli; Lolita, Lin Wong; King, Ching Hii; Paul Cliff, Simon Divis; Balbir, Singh (2020)
To monitor the incidence of Plasmodium knowlesi infections and determine whether other simian malaria parasites are being transmitted to humans, we examined 1,047 blood samples from patients with malaria at Kapit Hospital in Kapit, Malaysia, during June 24, 2013–December 31, 2017. Using nested PCR assays, we found 845 (80.6%) patients had either P. knowlesi monoinfection (n = 815) or co-infection with other Plasmodium species (n = 30). We noted the annual number of these zoonotic infections increased greatly in 2017 (n = 284). We identified 6 patients, 17–65 years of age, with P. cynomolgi and P. knowlesi co-infections, confirmed by phylogenetic analyses of the Plasmodium cytochrome c oxidase subunit 1 gene sequences. P. knowlesi continues to be a public health concern in the Kapit Division of Sarawak, Malaysian Borneo. In addition, another simian malaria parasite, P. cynomolgi, also is an emerging cause of malaria in humans.